Analisis Manajemen Pengelolaan Zakat Pada Badan Amil Zakat Nasional Kota Jambi - Habriyanto Habriyanto; Bambang Kurniawan; Alwaraah Alwaraah (STIKes Ibnu Sina Ajibarang, 2024)
The National Zakat Amil Agency is a zakat management organization formed by the government, consisting of elements of the community and government whose task is to collect, distribute and utilize zakat in accordance with religious provisions. The Jambi City National Zakat Amil Agency (BAZNAS) carries out the task of managing zakat at the city level. This research aims to analyze zakat management which consists of planning, organizing, reporting, directing and supervising zakat in Baznas Jambi City, to find out the obstacles that exist in the zakat management process in Baznas Jambi City, and to find out solutions in managing zakat in Baznas Jambi city. In this research, researchers used qualitative descriptive methods. To reveal this problem in depth and comprehensively, the author collected data through observation, interviews, documentation. The research results show that the implementation of zakat management in Jambi City Baznas is in accordance with management theory, where management theory consists of planning, organizing, reporting, directing and supervising. The implementation of zakat management in Baznas Jambi City has met the management theory standards. So the implementation of zakat management in Jambi City Baznas is quite good, even though zakat funds are still lacking, Jambi City Baznas continues to distribute zakat funds to parties who need them so that the benefits of zakat funds in Jambi City can be felt by the community as intended in the zakat law